Credit and usury in Jewish society in the Mishnah and Talmud - Rozenfeld, Ben Tsiyon (The Brill reference library of ancient Judaism, 2024)
"Credit is the oxygen of every society. In many cases we wonder why the rabbis prohibit certain business credit transactions considering them usury. The writer uses literary and epigraphic sources to decipher the rabbinic approach. This book shows how rabbinic legislation innovatively expand the Torah prohibition of usury in loans to all fields of credit. It is a pioneering inquiry regarding rabbinic literature compiled under Roman and Sasanid rule, helping to fill the void in research concerning credit. It also distinguishes various kinds of credit differentiating credit of money for money, or products, exposing the ramifications of the rabbinic legislation"--